Insights into the potential role of alpha1‐antitrypsin in COVID‐19 patients: Mechanisms, current update, and future perspectives. (12th July 2021) - Marzouk, Saber; Attia, Noha; Mashal, Mohamed
Abstract: In this work, we provide an up‐to‐date summary of the available molecular‐ and cell‐related mechanisms by which alpha1‐antitrypsin (AAT) protein could be of benefit in treating COVID‐19 patients. As well, we demonstrate the current status in terms of the ongoing clinical trials using AAT in COVID‐19 patients. Finally, we touch on the potential role gene therapy and stem cell‐based gene therapy could have in such emerging and serious condition caused by the SARS‐CoV‐2 virus.